2016
DOI: 10.1111/1556-4029.13129
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Palatal Rugae as a Forensic Marker in Orthodontically Treated Cases

Abstract: The palatal rugae have been used as a reference landmark and identification marker by orthodontists and forensic analysts. However, the reliability of palatal rugae as a forensic marker remains questionable once an individual is subjected to orthodontic treatment. This study aimed at evaluating the changes in the rugae pattern after nonextraction, extraction, and maxillary expansion orthodontic treatment. The lengths and shapes of palatal rugae were evaluated on the pretreatment and post-treatment dental casts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 11 publications
1
21
0
6
Order By: Relevance
“…First and foremost, it is necessary to identify stable structures within the oral cavity that can be used as reference points for superimposition of digital images. Among these, the palatine folds are the most frequently chosen [ 17 ], even though several studies have shown that their position and/or dimensions may vary in certain clinical conditions [ 18 ]. Furthermore, palatal structures may only be used as reference points in the upper jaw.…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost, it is necessary to identify stable structures within the oral cavity that can be used as reference points for superimposition of digital images. Among these, the palatine folds are the most frequently chosen [ 17 ], even though several studies have shown that their position and/or dimensions may vary in certain clinical conditions [ 18 ]. Furthermore, palatal structures may only be used as reference points in the upper jaw.…”
Section: Discussionmentioning
confidence: 99%
“…We used superimposition on palatal rugae, that have been proposed and considered as a stable reference, 24,25 and have been used as a reference structure to assess sagittal changes (eg, molar distalization) 26,27 and vertical changes (eg, molar eruption, when coupled to lateral cephalograms). 19 We used a mushroom area, already described in the literature, 15,26 As the palate does not represent an absolute reference and it may have remodeling toward oral cavity, the net value of eruption may be underestimated.…”
Section: Superimpositionsmentioning
confidence: 99%
“…Para a sobreposição de várias fotografias digitais para se comparar os padrões de rugas palatinas, usa-se também variados computadores e programas (Sunil et al, 2014). A tecnologia de digitalização tridimensional (3D) facilita a correspondência computadorizada dos padrões de rugas palatinas de forma segura e comprovada, comparável ao padrão ouro atual que avalia impressões digitais (Taneva, Kusnoto & Evans, 2015) Com base nos estudos levantados, verificamos a presença de dúvida relativa à interferência do uso de aparelhos ortodônticos no padrão das rugas, mas apesar disso a maioria dos estudos comprovou que a forma de rugas permaneceu consistente (Pateria & Thakkar, 2011;Taneva, Kusnoto & Evans, 2015;Ali, Shaikh & Fida, 2016). Um estudo apenas afirmou que o tratamento ortodôntico induz alterações morfométricas que podem dificultar a identificação humana baseada em rugas palatinas, mas não impedir (Mustafa, Allouh & Alshehab, 2015).…”
Section: Rugoscopia Palatinaunclassified